A Brief Discussion About Image Quality and SEM Methods for Quantitative Fractography of Polymer Composites. Issue 3 (22nd August 2012) - Hein, L. R. O.; Campos, K. A.; Caltabiano, P. C. R. O.; Kostov, K. G.
Summary The methodology for fracture analysis of polymeric composites with scanning electron microscopes (SEM) is still under discussion. Many authors prefer to use sputter coating with a conductive material instead of applying low‐voltage (LV) or variable‐pressure (VP) methods, which preserves the original surfaces. The present work examines the effects of sputter coating with 25 nm of gold on the topography of carbon‐epoxy composites fracture surfaces, using an atomic force microscope. Also, the influence of SEM imaging parameters on fractal measurements is evaluated for the VP‐SEM and LV‐SEM methods. It was observed that topographic measurements were not significantly affected by the gold coating at tested scale. Moreover, changes on SEM setup leads to nonlinear outcome on texture parameters, such as fractal dimension and entropy values. For VP‐SEM or LV‐SEM, fractal dimension and entropy values did not present any evident relation with image quality parameters, but the resolution must be optimized with imaging setup, accompanied by charge neutralization. SCANNING 35: 196‐204, 2013. © 2012 Wiley Periodicals, Inc.